Effect of collagen sponge and flowable resin composite on pain management after free gingival graft harvesting: A randomized controlled clinical trial - Meza-Mauricio, Jonathan (2023)
The aim of this study was to compare the effect of the application of a flowable resin composite coating, over a collagen sponge stabilized with suture, on postoperative pain after free gingival graft harvesting. Thirty-two free gingival grafts were harvested from the palate in 32 patients, who were subsequently randomized to have only a collagen sponge stabilized with sutures applied to the palatal wound (control), or to have the collagen sponge coated with a flowable resin composite (test). Patients were observed for 14 days, and the pain level was evaluated by using a numerical rating scale. The consumption of analgesics during the postoperative period and the characteristic of the graft were also analyzed. The patients in the test group reported having experienced significantly less pain statistically than the patients in the control group throughout the study. The consumption of analgesics was lower in the test group. The dimensions of harvested grafts in the control and test groups showed no significant differences in height, width, and thickness. In conclusion, the addition of flowable resin composite coating to the hemostatic collagen sponge on the palatal wound following free gingival graft harvesting helped to minimize postoperative pain.